The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1176/appi.ps.54.12.1629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Forensic Outcomes From the Illinois Mental Health Juvenile Justice Initiative

Abstract: S: By linking youths with significant mental health needs to existing community-based services, it appears possible both to ameliorate psychopathology and to reduce delinquency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…The recommended levels of care consider milieu intensity and service intensity. A more recent instrument, the Child and Adolescent Needs and Strength instrument (CANS), was patterned after the CASPI and has demonstrated concurrent reliability in field testing, and has been used to evaluate service use within public mental health and juvenile justice systems (Lyons, Griffith, Quintenz, Jenuwine, & Sasha, 2003;Lyons et al, 2004). However, both of these instruments are dependent on diagnostic categorization, which is often difficult to achieve in children due to lack of diagnostic clarity as well as high rates of co-morbidities.…”
Section: In Live System Of Care Clinical Settings the Calocus/casii mentioning
confidence: 99%
“…The recommended levels of care consider milieu intensity and service intensity. A more recent instrument, the Child and Adolescent Needs and Strength instrument (CANS), was patterned after the CASPI and has demonstrated concurrent reliability in field testing, and has been used to evaluate service use within public mental health and juvenile justice systems (Lyons, Griffith, Quintenz, Jenuwine, & Sasha, 2003;Lyons et al, 2004). However, both of these instruments are dependent on diagnostic categorization, which is often difficult to achieve in children due to lack of diagnostic clarity as well as high rates of co-morbidities.…”
Section: In Live System Of Care Clinical Settings the Calocus/casii mentioning
confidence: 99%
“…No study (that I have found) has specifically examined whether DAs intentionally drop out of community-based services or are forced to terminate services in response to placement in detention/prison or other treatment barriers. While it is likely a combination of several factors, the important point is that many DAs are not receiving mental health or substance-related services postdetention and are failing to benefit from the positive impacts of community-based mental health interventions (Hoeve et al, 2013;Lyons et al, 2003). …”
Section: Timing Of Treatment Services and Continuity Of Carementioning
confidence: 99%
“…It should be noted that approximately 87.8% of the DAs with prior treatment obtained these treatment services within the two years prior to being admitted into detention, so these youth likely remember their providers, are familiar with treatment, know where to seek treatment, etc., which eliminates many treatment barriers that may prevent DAs from seeking treatment after release from detention. Finally, the ease of service planning may account for the link between pre-and post-detention treatment; it may be easier for staff within the juvenile justice system to coordinate care with DAs' current (or past providers) in the community and make arrangements for these youth to continue services upon release from detention versus independently searching and finding providers for youth with no history of prior treatment (Lyons et al, 2003;Riley, 2014). …”
Section: Aim 2 Group Differences: Mental Health Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu çalışmalarda suçun gelişimi, suçun tekrarı ve bireyin topluma yeniden kazandırılması sürecinde ruhsal hastalıkların önemli etkisinin olduğu vurgulanmaktadır (2,3). Bu konuda giderek artan bilgilere rağmen psikiyatrik hastalıkların sıklığına yönelik veriler arasında ciddi uyumsuzluklar dikkati çekmektedir.…”
Section: Introductionunclassified